Workers' compensation claims related to natural rubber latex gloves among Oregon healthcare employees from 1987-1998 - Kammeyer-Mueller John; Horwitz Irwin B; McCall Brian P (BMC, 2002)
Abstract Background Occupational reaction to natural rubber latex (NRL) glove use by healthcare employees has been an area of increasing concern. Unfortunately, there is little data demonstrating the prevalence and severity of actual reactivity to NRL. Method Occupational reaction to NRL was estimated using workers' compensation claims filed by healthcare employees in Oregon for the period of 1987-1998. For the first ten years, these claims were estimated by source and conditions consistent with NRL glove reactions, while in the last two years a specific code developed in 1997 for NRL glove reactions was also employed. Results The claim rate was on average 0.58 per 10,000 healthcare workers annually, which constituted 0.29% of all workers' compensation claims. The most common condition experienced was dermatitis (80%) and most common body part affected was the hands (55.4%). The majority of claimants, 45 (69.2%), reported taking less than a month off work, suggesting most reactions were minor in nature, although one fatality was reported. The average NRL claim cost was $8,309.48. Overall the average cost per insured healthcare worker was approximately $0.50 per year. The occupational groups with the highest number of claims were nurses (30.8% of claimants) and nursing aides and orderlies (24.6% of claimants). Conclusions In comparison with other workers' compensation claims filed by healthcare workers during this period, 0.25% of the total was potentially related to NRL gloves. The rare incidence of respiratory and ocular claims is inconsistent with the hypothesis that asthmatic or conjunctival reactions to NRL gloves are common.